LITHOLOGICAL FEATURES OF THE BAZHENOV FORMATION OF NADYM-PURSKAYA OIL AND GAS FIELD ACCORDING TO THE DATA OF FLUORESCENT ANALYSIS - V Yu Abramov; A V Daniluk (RUDN Journal of Engineering Research, 2015)
In the article the peculiarities of the lithological structure of the Bazhenov formation in the Nadym- Purskiy oil and gas region according to the fluorescence core analysis. Результаты анализа сравни- ваются с данными геофизических исследований скважин. The results obtained are used in geological correlation of the results of drilling to Refine the geological boundaries and the allocation of oil reservoirs.